Medan Makna Ayat-ayat Pendidikan Inklusif dalam Al-Qur’an - Putra, Wahyu Hanafi; Mahmudah, Mahmudah; Musthofa, Tulus; Nasiruddin, Nasiruddin (Study Program of Arabic Language Teaching, 2023)
This research aims to analyze the meaning of inclusive education in QS. Al-Hujurat Verses 10-13. This research is qualitative with the type of library research. This research uses a semantic scientific approach. Research data is in the form of QS. Al-Hujurāt Verses 10-13 with Al-Qur'an data sources. Data collection techniques are carried out using documentation. The author documented every word and verse that refers to the meaning of inclusive education in the two letters and then presented them systematically for analysis. The data analysis for this research uses content analysis. The research results show seven pronunciations or sentences in the QS. Al-Hujurāt Verses 10-13 which have the main meaning of field of meaning, namely; Brotherhood; Faaṣliḥū baina akhawaikum; Lā Yaskhar; Walā Talmizū Anfusakum; Walā Tanābazū bil Alqāb; Lita’ārafū; and Atqākum. These seven pronunciations or sentences have a field of meaning according to the grouping of lexical domains, which are structural, associative, and collocative.